Parasite × vector relationship in Chagas disease: does Trypanosoma cruzi (Chagas, 1909) infection affect the spermatogenesis of Triatoma infestans (Klug, 1834)? - de Oliveira, Ana Beatriz Bortolozo [UNESP]; Tedeschi, Bianca Barbério Bogdan [UNESP]; de Oliveira, Jader [UNESP]; Madeira, Fernanda Fernandez [UNESP]; Falleiros Junior, Luiz Roberto [UNESP]; Silva Junior, Fernando César [UNESP]; da Rosa, João Aristeu [UNESP]; de Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP] (Springer Nature, 2020)
The parasite-vector interaction of Chagas disease is still poorly understood and the understanding of this relationship can help in the development of new strategies to control Trypanosoma cruzi transmission, which is the etiological agent of this disease. Considering the need to know if T. cruzi can cause some pathology in the reproductive system of the Chagas disease vectors, we investigated the spermatogenesis of Triatoma infestans infected by T. cruzi through histological and cytogenetic analysis. Trypanosoma cruzi Bolivia strain infection was not pathogenic for the reproductive system of T. infestans, because all the analyzed males had normal spermatogenesis, with all phases (spermatocytogenesis, meiosis and spermiogenesis) happening without any change. Thus, we demonstrated that the presence of T. cruzi Bolivia strain does not have influence in the spermatogenesis of T. infestans and we suggest that the influences on reproductive system observed for other species were a result of the action of the parasite on gametogenesis of females.
Keywords: Chagas disease; Reproduction; Triatomines; Vector-parasite relationship